2013
DOI: 10.1037/a0033019
|View full text |Cite
|
Sign up to set email alerts
|

Do we become a different person when hitting the road? Personality development of sojourners.

Abstract: International mobility is a prevalent life event that particularly affects university students. The aim of this longitudinal study was twofold: First, we examined the impact of international mobility on personality (Big Five) change, separating self-selection effects from socialization processes. Second, we extended prior analyses on the association between life events and personality development by investigating the mechanisms that account for socialization processes. In particular, we assessed whether indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
253
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 310 publications
(273 citation statements)
references
References 103 publications
15
253
2
3
Order By: Relevance
“…The former approach asserts that the Big Five personality traits (McCrae, 2004) are not subject to complete alterations in all five traits. Yet, individuals have been found to become more agreeable, conscientious, and emotionally stable during the passage from adolescence to adulthood, which is also a genetically confirmed finding through the study of twins (Roberts et al, 2005;Zimmermann & Neyer, 2013). Conversely, individual deviations from such trajectories have been documented in the research, thus contradicting the hereditability of personality traits (Roberts et al, 2005).…”
Section: 3mentioning
confidence: 46%
See 2 more Smart Citations
“…The former approach asserts that the Big Five personality traits (McCrae, 2004) are not subject to complete alterations in all five traits. Yet, individuals have been found to become more agreeable, conscientious, and emotionally stable during the passage from adolescence to adulthood, which is also a genetically confirmed finding through the study of twins (Roberts et al, 2005;Zimmermann & Neyer, 2013). Conversely, individual deviations from such trajectories have been documented in the research, thus contradicting the hereditability of personality traits (Roberts et al, 2005).…”
Section: 3mentioning
confidence: 46%
“…Social investments (e.g., work, study, marriage, family, social roles) are found to relate to increased scores on personality measures of "social dominance, agreeableness, conscientiousness, and emotional stability and to increases in these dimensions over time" (Roberts et al, 2005, p. 174). Also referred to as life events in the literature, the SIP accounts for individual differences in personality development, which can be related to individuals' "self-selection" of change rather than a biogenetic determinism (Zimmermann & Neyer, 2013). One example of a life event that has the potential to impact on personality development is residence abroad.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we explore the conditions that bring geographical mobility into effect as a moderator or mediator of person-environment associations within or between macro levels and individual levels of analysis. As previous research has paid scant attention to concurrent effects of personality traits and residential mobility experiences on proximal environmental characteristics, we complement our theoretical considerations with an empirical example from our own longitudinal research project PEDES-Personality Development of Sojourners (see Zimmermann & Neyer, 2013). With this example, we are able to show that, indeed, personality traits determine individuals' proximal social environment in terms of social relationship fluctuation and that these personality effects are, in part, due to individuals' self-selection in international mobility experiences.…”
mentioning
confidence: 99%
“…Students who went abroad for part of their university education report to be more independent, approachable and agreeable than before their stay. Furthermore, they are more open to foreign cultures and ways of working (Clarke et al, 2009;DAAD and HIS, 2013;Zimmermann and Neyer, 2013).…”
Section: Introductionmentioning
confidence: 99%